Walter B. Wriston and his wife, Kathryn Dineen Wriston (Tufts Archival Research Center, 2008)
4.4 x 3.7. This date is approximate. The image was created from 'Photograph (10)' from the CD titled 'Walter B. Wriston Photographs - CD 7'.